Rhetoric, persuasion, and modern legal writing : the pen is mightier - Porto, Brian L (Lanham : Lexington Books, 2020)
"Focusing on the opinion writing of Justices Holmes, Jackson, Black, Brennan, and Scalia, this book assesses the influence of rhetorical techniques traceable to ancient Greece on some of the most iconic opinions in Supreme Court history"
Includes bibliographical references (pages 185-190) and index
Keywords: Judicial opinions -- United States; Legal composition